Pengembangan Soal High Order Thingking Skill Matematika SMP - Nugraha, Andri; Meika, Ika; Yunitasari, Ika (Universitas Mathla'ul Anwar Banten, 2024)
The aim of this research is to develop valid and practical HOTS (High Order Thinking Skill) questions on the topics of probability and linear equations in two variables for eighth-grade students. This study employs Research and Development (R&D) methodology, utilizing both qualiative and quantitative approaches. The development model used in this research is Tessmer’s formative research model, which includes the stages of preliminary, self-evaluation (analysis of the curriculum, students, materials, and design), and prototyping (expert review, one-to-one, and small group). The results of the development of HOTS questions on probability and linear equations in two variables for eighth-grade students at SMP Negeri 1 Sobang yielded a validity score from the validators of 3.46, indicating that the HOTS questions, as assessed in the small group phase (with 6 students), achieved a score of 84.5%. which falls under the practical criteria.